Comparison of clinicopathological features in incidental and nonincidental papillary thyroid carcinomas in 308 patients - Nuray Can (Polish Journal of Pathology, 2017)
Incidental papillary thyroid carcinomas (IPTCs) consist of a significant portion of increasing incidence in papillary thyroid carcinomas. This study investigated the clinicopathological features of IPTCs from different perspectives and by comparing nonincidental PTCs (NIPTCs) in patients who underwent total thyroidectomy and lymph node dissection. Basic results were as follows. IPTC was present in 27.9% of 308 patients. IPTCs were significantly accompanied by lymphocytic thyroiditis (LT), particularly, multinodular hyperplasia (MNH). IPTCs were more common in older patients (51.3 years vs. 47.2 years) and in female patients. IPTCs significantly differed from NIPTCs in terms of smaller tumour size, lymphatic vessel invasion (2.6% vs. 97.4%), extrathyroidal extension (4.3% vs. 95.7%), lymph node metastasis (3.6% vs. 96.4%), multifocality (21.2% vs. 78.8%), bilaterality (5.3% vs. 94.7%), and BRAFV600 mutation (6.7% vs. 93.3%). Older age, bilaterality, encapsulation, and radioactive iodine (RAI) were significantly more common in IPTCs > 5 mm than in those ≤ 5 mm. In conclusion, IPTCs are more commonly associated with LT and MNH. IPTCs may have a more favourable prognosis than NIPTCs, and tumour size > 5 mm may predict bilaterality and need for RAI. Nevertheless, the patient-based clinical approach in IPTCs may have benefits in the management of IPTCs.